Pengaruh Pengelolaan Konten Instagram @Lakespra Terhadap Respon Audiens - Viosela Meytriana Situmorang; Burhanuddin Burhanuddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The development of digital communication technology has encouraged health institutions to utilize social media as a medium for health promotion and information dissemination. This study aims to analyze the effect of Instagram content management on audience responses at Lakespra dr. Saryanto. The research used a quantitative approach with a survey method involving 60 respondents selected from members of Lakespra dr. Saryanto. Data were collected through questionnaires distributed online and analyzed using validity tests, reliability tests, descriptive statistics, and simple linear regression with IBM SPSS Statistics. The results showed that all questionnaire items were valid and reliable, with Cronbach’s Alpha values of 0.951 for the content management variable and 0.934 for the audience response variable. The regression analysis indicated that Instagram content management had a significant effect on audience responses, with a significance value of 0.000 and an F value of 184.783. The coefficient of determination showed that Instagram content management contributed 76.1% to audience responses, including engagement, understanding of health information, and interest in health services. The findings indicate that visually attractive, informative, and consistent Instagram content can improve audience interaction and support digital health communication effectively.